2021
DOI: 10.1108/tpm-10-2020-0085
|View full text |Cite
|
Sign up to set email alerts
|

Impact of shared leadership on team performance through team reflexivity: examining the moderating role of task complexity

Abstract: Purpose To react quickly and to be flexible to respond to environmental uncertainty, working in teams is preferable. However, leadership must be decentralised for effective team performance. This paper aims to examine the impact of shared leadership on team performance through team reflexivity with task complexity. Design/methodology/approach To test the hypothesised relationships, a quantitative research design with purposive sampling technique was used. Data were gathered from employees working in teams. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…Aubé et al (2018) concluded that shared leadership can improve team functioning, thus predisposing members to attain the highly gratifying and productive flow state. By accepting the "nagging" the football players in the currents study also took on a role in contributing to the ideas in a more detailed manner and thereby accepting a shared leadership (Duguay et al, 2020) by taking on the players part of the responsibility shared leadership is associated with team creativity (Xie et al, 2021) and team reflexivity (Hadi and Chaudhary, 2021).…”
Section: Resultsmentioning
confidence: 96%
“…Aubé et al (2018) concluded that shared leadership can improve team functioning, thus predisposing members to attain the highly gratifying and productive flow state. By accepting the "nagging" the football players in the currents study also took on a role in contributing to the ideas in a more detailed manner and thereby accepting a shared leadership (Duguay et al, 2020) by taking on the players part of the responsibility shared leadership is associated with team creativity (Xie et al, 2021) and team reflexivity (Hadi and Chaudhary, 2021).…”
Section: Resultsmentioning
confidence: 96%
“…1. We should note that both team trust and team learning behavior play mediating roles in the shared leadership–team performance relationship (e.g. Drescher et al ., 2014; Ul Hadi and Chaudhary, 2021), but since the sequential mediating effect is the focus of this study, we do not derive separate mediation hypotheses for trust and learning.…”
Section: Notesmentioning
confidence: 99%
“…We should note that both team trust and team learning behavior play mediating roles in the shared leadership-team performance relationship (e.g. Drescher et al, 2014;Ul Hadi and Chaudhary, 2021),…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Developing a charter including elements such as operating guidelines, behavioral norms and performance management processes, in conjunction with teams’ periodical review and revision of the charter as needed, results in increased quality of team activities (Hunsaker et al , 2011). Discussing team processes, strategies and objectives contributes to team reflexivity, empowerment and, ultimately, their performance (Hadi and Chaudhary, 2021). Therefore, it is crucial to equip teams to develop charters that either incorporate communication and conflict resolution plans or to create these plans independently.…”
Section: Literature Reviewmentioning
confidence: 99%